Managing agrosilvopastoral systems: promoting versatile tree species: Senegalia mellifera (Benth.) Seigler & Ebinger.: A valuable tree that provides numerous resources to local people - Louhaichi, Mounir; Gamoun, Mouldi (International Center for Agricultural Research in the Dry Areas, 2024)
This factsheet provides essential information about Senegalia mellifera, commonly known as Black Thorn, focusing on its origin, establishment, benefits, and maintenance. Native to diverse regions of Africa, this resilient tree has ecological, agricultural, and economic significance. Learn about its preferred growing conditions and the valuable benefits. Discover key insights into establishing and maintaining Senegalia mellifera for optimal growth and sustainable use.